Platelet-Rich Plasma in the Treatment of Subcutaneous Venous Access Device Scars: A Head-to-Head Patient Survey. (24th March 2015) - Eichler, C.; Najafpour, M.; Sauerwald, A.; Puppe, J.; Warm, M.
Abstract : Introduction . Platelet-rich plasma (PRP) is a product widely used in sports medicine, tissue repair, and general surgery. A recent meta-analysis showed this product to be beneficial when introduced into a wound area, be it intra-articular (i.e., joint-injections) or direct introduction onto the wound surface. Methods . Between the years of 2012 and 2014 a questionnaire evaluating surgical outcome after port (venous access device) removal was answered by 100 patients in the control group and 20 patients in a PRP group, leading to a total of 120 patients in this single center, retrospective, subjective outcome evaluation. Results . No statistical difference was shown in postsurgical complication rates, postsurgical pain, decreased mobility, and overall quality of life. A significant difference was shown in overall patient satisfaction and the desire to further improve port area scarring. Results differed significantly in favor of the PRP group. Interestingly, approximately 40.2% of patients are dissatisfied with the surgical outcome after port removal in the control group. This result, though surprising, may be improved to 10% dissatisfaction when a PRP product is used. Conclusion . PRP products such as Arthrex ACP are safe to use and present an additional option in improving surgical outcome.